The Effect Of The Team Games Tournament (TGT) Cooperative Learning Model On Fourth-Grade Students' Learning Outcomes In Pancasila Education - Meilaniska Meilaniska; Arna Juwairiyah; Erwin Eka Saputra (CV. Gerasi Insan Nusantara, 2025)
This study examined the effect of the Team Games Tournament (TGT) cooperative learning model on fourth-grade students' learning outcomes in Pancasila Education. The study was motivated by the need to improve student achievement through more active, collaborative, and engaging instructional practices. A quantitative approach with a quasi-experimental two-group pretest–posttest design was employed. The study involved an experimental class that received instruction using the TGT model and a control class that received conventional instruction. Data were collected using validated and reliable multiple-choice tests administered as pretests and posttests. The data were analyzed using descriptive statistics and an independent-samples t-test with SPSS 26 for Windows. The results showed that the mean score of the experimental class increased from 68.18 on the pretest to 86.14 on the posttest, representing a gain of 17.96 points. Meanwhile, the control class mean increased from 59.40 to 72.40, representing a gain of 13.00 points. The independent-samples t-test produced a significance value of 0.000 < 0.05, indicating a statistically significant difference in learning outcomes between the two classes. These findings demonstrate that the Team Games Tournament (TGT) cooperative learning model had a significant positive effect on fourth-grade students' learning outcomes in Pancasila Education. TGT is therefore recommended as an active, collaborative, and engaging alternative instructional model for improving learning outcomes in elementary Pancasila Education.